69th Issue Info Kampus UiTM Sarawak Buletin : Januari 2015 / Professor Dato Dr. Jamil Hj Hamali... [et al.] - Hj Hamali, Professor Dato Dr. Jamil; Abdullah, Professor Dr. Firdaus; Wee, Roselind; Lau, Ung Hua; Metom, Lilly; Abg Bohari, Dayang Faridah; Johari, Aiza; Abang, Mohamad; Ch'ng, Lool Chin; Yeo, Jacinta Jiin Yih; Sarkawi, Adib; Karim, Abdul Khalid; et al. (Universiti Teknologi MARA Cawangan Sarawak, 2015)
A very happy 2015 to UITM staff and students. I would like to express my deepest appreciation to the Chief Minister of Sarawak, Yang Amat Berhormat Dato Patinggi Tan Sri (Dr) Haji Adenan bin Haji Satem and the Vice - Chancellor of UITM,Yang Berbahagia Tan Sri Dato' Sri Professor Ir. Dr. Sahol Hamid Abu Bakar, FASc for the continues support given to UITM Sarawak.To the staff, i thank you all for your cooperation and dedication which have contributed to the tremendous development made by UITM Sarawak.In addition, i also encourage UITM Sarawak student to work hard and excel in their studies.